Polymer-derived ceramic tapes with small and negative thermal expansion coefficients. Issue 2 (February 2018) - Fedorova, A.; Michelsen, L.; Scheffler, M.
Abstract: A polysiloxane filled with ß-eucryptite and/or SiC was used for the processing of polymer derived ceramic tapes. The combination of both fillers in varying proportions allowed to tailor the overall bulk thermal expansion and the flexural strength of the resulting composite materials simultaneously. Incorporation of SiC increased noticeably the flexural strength of the samples and influenced the phase changes resulting from the interactions between the β-eucryptite filler and the polymer derived ceramic matrix. Changes in the phase composition and changes of the unit cell parameters of β-eucryptite because of the formation of solid-solutions with silica originating from the SiO2 constituent of the polymer derived ceramic matrix were observed by Rietveld refinement. Tapes resulting from this process possess a sufficient mechanical stability and their coefficient of thermal expansion can be adjusted from slightly positive to moderate negative values.